The Resilience of a Coastal Tourist Destination: An Analysis of Pangandaran's Tsunami Risk - Marpaung, Grace; Rahayu, Harkunti Pertiwi (Politeknik Negeri Bandung, 2025)
Pangandaran Beach, designated as a Regional Tourism Strategic Area under the Pangandaran Regency Tourism Master Plan 2018–2025, encompasses several key zones, including West and East Beaches, the Nature Reserve Tourism Park, Pananjung Seafood Tourism Centre, and Pananjung Tourist Village. This study investigates the resilience level of the tourism industry within the Pangandaran Beach area by applying a framework of seven tourism resilience elements: 1) Risk Understanding, 2) Business Operations, 3) Disaster Preparedness, 4) Mitigation Planning, 5) Response and Recovery, 6) Infrastructure and Environment, and 7) Governance and Institutions. Seventy tourism industry stakeholders were surveyed using stratified random sampling with a 90% confidence level and a 10% margin of error. The analysis employed descriptive quantitative methods and Importance-Performance Analysis (IPA). Findings reveal that three key resilience attributes fall into the low-performance quadrant: Disaster Mitigation (DM1), Evacuation Planning (DM2), and Building Structure (E1). Despite efforts by the local government and the Regional Disaster Management Agency (BPBD) to promote disaster risk reduction, DM1 and DM2 remain under-implemented due to industry concerns about potentially deterring tourists. Furthermore, E1 remains underdeveloped due to high renovation costs. Although the overall resilience level is moderate, enhancing stakeholder awareness and investment in disaster preparedness is crucial to strengthening the region's capacity to withstand tsunami-related risks.